1984
DOI: 10.1063/1.95200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress relaxation on the generation of radiation-induced interface traps in post-metal-annealed Al-SiO2-Si devices

Abstract: We have found experimentally that both the interfacial stress distribution and the generation of interface traps in an Al-SiO2-Si structure change systematically with time lapse between post-metal-anneal treatment and x-ray irradiation, and strong correlation between the two is established. The results suggest that the device radiation sensitivity is modulated by the interfacial stress and/or the oxide bond strain gradient. Two possible mechanisms based on the variations of the interfacial strained bonds are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…is stretched to nm, near-midgap states can open up that may at least metastably capture an electron, with the energetics of capture becoming more favorable with increasing Si-Si spacing [10], [119]. These kinds of stretched Si-Si bonds are likely to exist preferentially near the interface [10], [125], in which a significant amount of strain must be accommodated [125], [133], [136]- [141]. When an electron is captured, the Si-Si spacing decreases due to the increased electron density between the two atoms.…”
Section: B Defect Microstructures and Energiesmentioning
confidence: 99%
“…is stretched to nm, near-midgap states can open up that may at least metastably capture an electron, with the energetics of capture becoming more favorable with increasing Si-Si spacing [10], [119]. These kinds of stretched Si-Si bonds are likely to exist preferentially near the interface [10], [125], in which a significant amount of strain must be accommodated [125], [133], [136]- [141]. When an electron is captured, the Si-Si spacing decreases due to the increased electron density between the two atoms.…”
Section: B Defect Microstructures and Energiesmentioning
confidence: 99%
“…The increase in Pbl centers may be a result of polished-induced stress changes at the Si02/Si interface. It has been reported that radiation-induced interface-trap buildup can be affected strongly by interfacial stress [20,21]. Even though the EPR measurements suggest that CMP has affected the interface, the electrical role of the P b l center remains unresolved.…”
Section: In Results and Discussionmentioning
confidence: 98%
“…These results indicate that the Si/SiO interface of the WSi sample is less susceptible to, and less damaged by the -ray irradiation than compared with the CoSi sample. Since applying compressive stress at the Si/SiO interface has been found to reduce the generation of interface-trap-density by ionizing radiation [10], [11], we attribute this phenomenon to the fact that two additional annealing steps for forming CoSi enhances the interfacial tensile stress, and therefore increases the interface-trap-density after irradiation. An oxide trapped charge is produced as well by ionizing radiation and causes the -curves to shift along the voltage axis.…”
Section: Methodsmentioning
confidence: 98%